Avoided emissions resulting from grid-tied solar photovoltaic generation in the Philippines: an energy-based analysis. Issue 1 (February 2021) - Enano, Nelson Jr; Barroca, Renyl; Montecastro, Doris
Abstract: One of the motivations of deploying renewable energy is its promise to reduce emissions. The accounting of emissions, however, becomes challenging and complex in the case of grid-tied PV system as it also derives energy from the centralized grid where the energy comes from a mix of resource. The amount of avoided emissions is highly variable. The study focused on the determination of avoided emissions resulting from grid-tied solar photovoltaic (PV) generation of Ateneo de Davao University Jacinto Campus in the Philippines. The results show that the small size of PV systems impacts only the marginal generating plant which is normally a hydro, diesel or natural gas-fired generator and largely depends on which grid the consumer is located. It shows that the energy generation of the PV acts like a peak shaving mechanism that reduces the system load. The solar PV of the university was simulated and the avoided emissions (CO2, SO2, NOx, PM10, PM2.5, NH3, VOCs, and Hg) were quantified through energy-based approach.